Parameters of the systemic inflammatory response and their relationship with atrial fibrillation in patients with ST-elevation myocardial infarction after percutaneous coronary intervention - B. I. Geltser; K. I. Shahgeldyan; R. L. Pak; I. G. Domzhalov; E. An. Kokarev; V. N. Kotelnikov (Российский кардиологический журнал)
Aim. To assess the predictive potential of inflammatory response indicators for risk stratification of newonset atrial fibrillation (AF) in patients with STelevation myocardial infarction (STEMI) after percutaneous coronary intervention (PCI).Material and methods. We analyzed data from 4152 electronic health records of patients with STEMI (2858 men and 1294 women). Two following groups were identified: the first group included 3781 (91,1%) patients without cardiac arrhythmia (CA), while the second group included 371 (8,9%) patients with newonset AF after PCI (POAF). The state of coronary flow after PCI was assessed using the thrombolysis in myocardial infarction (TIMI) score. Previously developed (neutrophil/lymphocyte (NLR), platelet/lymphocyte (PLR), monocyte/lymphocyte (MLR), systemic immune inflammation index (SII), systemic inflammatory response index (SIRI) and systemic inflammation total index (AISI)) and novel inflammatory response indicators (neutrophil/eosinophil ratio (NER) and neutrophil/basophil ratio (NBR)) were calculated.Results. In patients with STEMI with AF and without CAs after PCI with different TIMI levels indicated more pronounced inflammatory response changes with a combination of POAF and TIMI <3. The highest predictive potential for POAF was demonstrated by neutrophil rate >75% (odds ratio (OR)=2,57; AUC=0,779), NLR >6,29 (OR=2,61; AUC=0,757), eosinophil rate <0,21% (OR=2,74; AUC=0,739), AISI (OR=2,14; AUC=0,737), NBR (OR=2,29; AUC=0,727) and NER (OR=2,49; AUC=0,725). MLR and PLR had lower predictive power.Conclusion. In patients with STEMI and POAF, the intensity of the systemic inflammatory response is significantly higher than in individuals without CAs. The prognostic potential of the novel inflammatory response indicators (NER and NBR) was comparable to the classical ones (NLR, SII, SIRI, AISI).